Flash floods in Catalonia: a recurrent situation - M. C. Llasat; M. Llasat-Botija; A. Rodriguez; S. Lindbergh (Advances in Geosciences, 2010)
This work focuses on the analysis and characterization of the flash flood events occurring during summer in Catalonia. To this aim, a database with information about the social impact produced by all flood events recorded in Catalonia between 1982 and 2007 has been built. The social impact was obtained systematically on the basis of news press data and, occasionally, on the basis of insurance data. Flood events have been classified into ordinary, extraordinary and catastrophic floods, following the proposal of Llasat et al.~(2005). However, bearing in mind flash flood effects, some new categories concerning casualties and car damage have also been introduced. The spatial and temporal distribution of these flood events has been analyzed and, in an effort to better estimate the social impact and vulnerability, some indicators have been defined and analyzed for a specific region. These indicators allow an analysis of spacial and temporal trends as well as characterization of the events. Results show a flash-flood increase in summer and early autumn, mainly due to inter-annual and intra-annual changes in population density.